2003
DOI: 10.1108/eb028960
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Relationship of Employee Involvement With Job Satisfaction, Employee Cooperation, and Intention to Quit in U.S. Invested Enterprise in China

Abstract: In a U.S. invested enterprise in China, the receptivity of Chinese employees to a participative work environment was examined. Structural equation analysis indicated support for a model in which job satisfaction mediates the relationships between elements of a participative work environment (i.e., tasks performed, the relationships individuals had with their work groups, and the nature of the decision making processes) and employee willingness to cooperate with co‐workers and intention to quit. Task interdepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 56 publications
4
76
0
9
Order By: Relevance
“…Although people in small power distance cultures tend to value work autonomy and freedom, people in high power distance cultures, such as China, tend to take hierarchical inequalities for granted (Aycan, Kanungo, & Sinha, 1999;Earley & Stubblebine, 1989;Hofstede, 1991;Mak, 1998;Nasierowski & Mikula, 1998). It is also suggested that they have been exposed to, have become tolerant of, and have even submitted to authoritarian and command-based leadership for decades (Hofstede, 2001;Schermerhorn & Nyaw, 1990;Scott et al, 2003;Walder, 1986). Eylon and Au (1999) reported that open communication and employee participation did not lead to increased job satisfaction and job performance for people in high power distance cultures.…”
Section: Potential Deviations Of Conflict Management Styles In the Chmentioning
confidence: 99%
See 1 more Smart Citation
“…Although people in small power distance cultures tend to value work autonomy and freedom, people in high power distance cultures, such as China, tend to take hierarchical inequalities for granted (Aycan, Kanungo, & Sinha, 1999;Earley & Stubblebine, 1989;Hofstede, 1991;Mak, 1998;Nasierowski & Mikula, 1998). It is also suggested that they have been exposed to, have become tolerant of, and have even submitted to authoritarian and command-based leadership for decades (Hofstede, 2001;Schermerhorn & Nyaw, 1990;Scott et al, 2003;Walder, 1986). Eylon and Au (1999) reported that open communication and employee participation did not lead to increased job satisfaction and job performance for people in high power distance cultures.…”
Section: Potential Deviations Of Conflict Management Styles In the Chmentioning
confidence: 99%
“…Consequently, a leader has the right to maintain strong authority over subordinates, and the subordinates are obligated to obey. Prior studies have suggested that the communist tradition in China has given rise to a more command-based leadership behavior that emphasizes the loyalty and discipline of followers (Schermerhorn & Nyaw, 1990;Scott, Bishop, & Chen, 2003;Walder, 1986). In addition, compared with Western countries, China has a larger power distance culture that predisposes people to take the inequality between the powerful and the powerless for granted (Hofstede, 2001;House, Hanges, Javidan, Dorfman, & Gupta, 2004).…”
mentioning
confidence: 99%
“…It focuses on effective storage and segregation of things is done (Gupta and Jain, 2014). Every employee enjoys their work in a clean and healthy environment which raises confidence (Scott et al, 2003). The high standard of workplace organisation can be ensured by standardisation (Lingareddy et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Thirdly, the contingency model predicts that different outputs for PDM depend on the work situation. Scott et al (2003) suggested an environment in order that PDM increases employee satisfaction: (1) there is a willingness from employees to accept suggestions from others about their work; (2) PDM should improve employee commitment and feelings of ownership; (3) personal inputs from others improve employee positive feelings about their job; (4) people feel they have a responsibility to their work; (5) people enjoy the chance to interact with others during their tenure; and (6) the more lecturer participates in decision-making, the higher level he/she will commit to his/her organization. Ladd et al (2006) and Bhatti and Qureshi (2007) stated that participation promote lecturerloyalty to an organization.…”
Section: Accepted Rejectedmentioning
confidence: 99%